Analisis Determinan Kelemahan Pengendalian Intern Pemerintah Daerah Kabupaten/Kota Provinsi Jawa Timur - Alawiyah, Tina Tuti; Sumardjo, Mahendro; Darmastuti, Dewi (Institut Bisnis dan Informatika Kesatuan, 2020)
This study aims to determine the effect of local government size, local revenue (PAD), capital expenditure, and population on weaknesses in internal control in local governments. This research was carried out using multiple linear regression analysis on 104 samples of district / city governments in the province of East Java during 2016-2018, the results showed that there was no significant effect related to local government size, capital expenditure, and population on weakness in control. intern in local government. The size of the local government, the capital expenditure, and the population do not ensure that the internal control weaknesses owned by the regional government are small or large. Meanwhile, PAD has a significant positive effect on the weakness of internal control in local government. The amount of PAD has the potential to encourage managers to commit irregularities in regional financial management, thereby increasing the findings of weaknesses in local government internal control. Keywords: size of local government; PAD; capital expenditure; population; weaknesses of internal control.